Some ISIS-Software History and Technical Background on the new FOSS Integrated Library System ABCD - de Smet, Egbert (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
While free and open source software is gaining momentum in library automation, it is still not a trivial event to launch a full-blown integrated library system (ILS), given today's high demands on such library systems. In this article we describe the ISIS-software origins of the newly launched ABCD-software for which there is a morethan-average interest in many parts of the libraries and information communities in the developing world. Many — especially younger — librarians in the West have never heard about ISIS, its relevance and its technological concepts, so we will try to shed some light on this in order for librarians to better judge the meaning of the ABCD software for international librarianship and — why not — perhaps even for their own purposes.